Effects of different pelleting technologies and parameters on pretreatment and enzymatic saccharification of lignocellulosic biomass. (December 2021) - Gong, Chunxiao; Thomsen, Sune Tjalfe; Meng, Xianzhi; Pu, Yunqiao; Puig-Arnavat, Maria; Bryant, Nathan; Bhagia, Samarthya; Felby, Claus; Ragauskas, Arthur J.; Thygesen, Lisbeth Garbrecht
Abstract: Densification of lignocellulosic biomass is beneficial for its logistics, and in some situations, also for its application in biorefineries. In this study, industrial pellets and laboratory-made pellets produced at different die temperatures (90, 125 °C) from wheat straw, beech, and pine were pretreated (by dilute acid and alkali) and enzymatically hydrolyzed to study the effects of pelleting on pretreatment and sugar yield. The results showed that industrial pelleting positively affected sugar yield of the three biomasses for both acid and alkaline pretreatments, while laboratory pelleting affected sugar yield differently related to pretreatment types and biomass species. Pelleting disturbed biomass cell wall structure and affected the stability of hemicellulose and β-O-4′ linkages in lignin. The extent of hemicellulose solubility during acid pretreatment and the amount of lignin β-O-4′ ether linkages present in acid pretreated substrates could serve as indicators of the effect of pelleting on sugar yield. The structural modifications caused by pelleting and their effects on the enzymatic sugar yield correlate tightly to pelleting technology, pretreatment method, and biomass species. The discrepant effects between industrial and laboratory pelleting on sugar yield observed in this study should be considered when designing future studies. Graphical abstract: Image 1 Highlights: Pelleting affects the stability of hemicellulose and β-O-4′ linkages in lignin. The β-O-4′ content in acid pretreated substrates correlates well with sugar yield. Industrial pelleting enhances the sugar yields of wheat straw, beech and pine.